Effect of DA-9701 on the Gastrointestinal Motility in the Streptozotocin-Induced Diabetic Mice - Changyoon Ha (MDPI AG, 2021)
Background: Compared to the general population, diabetic patients experience more frequent episodes of gastrointestinal (GI) motility dysfunction, owing to the disruption of functional innervations. DA-9701 is a new prokinetic agent formulated from the extracts of Pharbitidis semen and Corydalis tuber. Aim: To investigate the effect of DA-9701 on GI motility in an animal model of streptozotocin (STZ)-induced diabetes. Methods: Diabetes was induced in mice by intraperitoneal injection of STZ (40 mg/kg of body weight in 0.1 M citrate buffer) for 3 days. Diabetic mice were divided into four groups and administered DA-9701 in different doses (1, 3, and 10 mg/kg) or placebo for 2 weeks. Intestinal transit was assessed using charcoal meal movement. GI isometric contraction was measured by applying an isometric force transducer on a circular muscle strip of the antrum, ileum, and proximal colon of sacrificed mice. Gastric emptying rate was evaluated by measuring the dye percentage remaining in the stomach relative to the total dye amount recovered in a standardization group of mice. Results: Body weight and antral and small intestinal motility were less in diabetic mice than in control mice, and colonic motility was similar in both. DA-9701 showed a dose-dependent increase in the amplitude of spontaneous phasic contractions in the antrum, ileum, and colon in diabetic mice without influencing body weight or blood glucose levels. The degree of improvement was comparable between diabetic and control mice. Intestinal transit was significantly more delayed in diabetic mice than in controls (43 ± 7% vs. 67 ± 8%, p < 0.05); however, DA-9701 restored the delayed intestinal transit more effectively compared to placebo (75% vs. 50%). The gastric emptying rate was significantly more delayed in diabetic mice than in controls (43 ± 10% vs. 62 ± 12%, p < 0.05), and was improved by DA-9701 in a dose-dependent manner (50%, 55%, and 60% in mice treated with 1, 3, and 10 mg/kg of DA-9701, respectively, vs. 43% in placebo-treated and 60% in control mice). Conclusions: DA-9701 improved GI contractility without affecting blood sugar and body weight in diabetic mice. DA-9701 could improve the decreased GI motility and clinical symptoms in progressive diabetic patients.